Enhancing EFL Listening Through Structured Autonomous Use of British Council Learn English Audio Materials - Yeni Daniarti; Muhammad Arie Firmansyah; Dedy Alamsyah (International Journal of Research in Education, 2026)
Listening proficiency often lags behind other English skills for EFL university students, particularly in engineering programs where limited class hours restrict systematic practice. While previous studies have highlighted the benefits of podcasts and online audio resources for developing listening skills, most of these studies have relied on short-term, teacher-led classroom interventions and have rarely structured learners’ autonomous engagement with a specific platform. This study aimed the effect of independent engagement with the British Council LearnEnglish audio series on the listening proficiency of autonomous EFL learners in an informatics engineering program. Furthermore, there is limited quasi-experimental evidence on the impact of guided independent listening programs using the British Council LearnEnglish audio series on university students' listening proficiency, especially in Indonesian higher education contexts. The experimental group (n = 15) received eight weeks of independent listening alongside regular instruction, while the control group (n = 15) received only regular instruction. A 40-item standardized listening test was administered pre- and post-test, and gain scores were analyzed using an independent samples t-test. The results revealed substantially greater proficiency gains for the experimental group, demonstrating the intervention's superior efficacy over conventional approaches. These results suggest that a structured, autonomous listening program using the British Council's LearnEnglish series can significantly improve listening proficiency in engineering-based English as a foreign language (EFL) programs with limited classroom time. Therefore, future research should examine long-term retention and cross-disciplinary scalability.